An Internet of Things (IoT) based Plant Irrigation and Monitoring System for Chili Plant - Ariffin, Nainunis; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2021)
This paper focused on irrigation control and a proper monitoring system to ensure that the plant receives enough nutrients and moisture at all times. Soil moisture and pH level are the two types of parameters that are being monitored. To maintain long-term smart farming solutions, a systematic approach to monitoring and controlling these parameters is required. The main objective of this project is to develop an Internet of Things-based chili plant irrigation and monitoring system (IoT). The implementation of IoT in this project also included using a Wi-Fi node as a connection medium. The data send soil moisture and pH levels to the user via the Blynk app and controls the water pump. Thus, a remote IoT platform could be used to automate irrigation and monitor crop status. It is successfully implemented to solve the problems faced by farmers.